A Framework for Rebuilding Trust in Social Automation Across Health-Care Domains. Issue 1 (June 2015) - Marinaccio, Kaitlyn; Kohn, Spencer; Parasuraman, Raja; De Visser, Ewart J.
This paper reviews current human-automation trust and trust repair literature as it applies to health-care systems. In addition, we examine the increased use and relevance of social agents, such as robots and virtual agents, within the medical field and consider the importance of using social agents in this particular domain. Furthermore, we examine strategies for trust repair following errors in health-care settings, and provide a conceptual framework for repairing trust with social automation. Most literature to date stems from a human-human perspective, and we hope to extend this work to the field of social automation. If these strategies are effective, humanautomation systems in health-care can maintain appropriate levels of trust, ensuring effective and efficient long-term collaborations in critical work areas.